Staffing and Working Conditions of Employees in Chinese Restaurants in Zimbabwe- Justifiable - Cleopas Njerekai; Rudorwashe Wushe; Vitalis Basera (Academic Journals, 2023)
This paper tests the validity of a barrage of grossly unfair labour practices levelled against Chinese investmentsin many African countries including Zimbabwe by extant literature and claims by ordinary citizens in the continent.The researchers noted that these labour mal-practices were mainly based on studies in the mining, construction,agriculture, transport, clothing and telecommunications sectors and was left wondering how manifest and justifiablethey were in Chinese restaurant investments in Zimbabwe whose visibility had highly increased in the last decade.A survey of 9 out of 10 registered Chinese restaurants was undertaken and 54 key informant employees were theresearch respondents. Researcher administered questionnaires and direct observation were the key data collectionmethods. This research demonstrated that most of the labour mal-practices levelled against Chinese investmentsin Zimbabwe were actually justifiable in the prevailing operating environment in country. The research suggests thatfurther research be carried out to determine the overall multiplier effects of these Chinese restaurants to the country.